2010
DOI: 10.1111/j.1939-1676.2009.0386.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Reporting of Clinical Trials of Dogs and Cats and Associations with Treatment Effects

Abstract: Background: To address concerns about the quality of reporting of randomized controlled trials, and the potential for biased treatment effects in poorly reported trials, medical journals have adopted a common set of reporting guidelines, the Consolidated Standards of Reporting Trials (CONSORT) statement, to improve the reporting of randomized controlled trials.Hypothesis: The reporting of clinical trials involving dogs and cats might not be ideal, and this might be associated with biased treatment effects.Anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 38 publications
6
69
1
Order By: Relevance
“…Finally, key methodological domains were underreported in veterinary RCTs compared with those in medical RCTs (research question 3). This latter finding is critical as under-reporting of methodological domains in veterinary RCTs has been associated with increased treatment effects (Sargeant et al, 2010). Observational non-randomized articles are fundamental in certain stages of the development of interventional procedures (Schünemann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, key methodological domains were underreported in veterinary RCTs compared with those in medical RCTs (research question 3). This latter finding is critical as under-reporting of methodological domains in veterinary RCTs has been associated with increased treatment effects (Sargeant et al, 2010). Observational non-randomized articles are fundamental in certain stages of the development of interventional procedures (Schünemann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In a subset of 63 RCTs on dogs and cats, Brown (2007) reported that most RCTs with losses to follow-up did not account for these losses in the data analysis and did not acknowledge the potential impact on the outcomes of these RCTs. Another study found substantive deficiencies in the reporting of key methodological domains in RCTs with dogs and cats published between 2006and 2008(Sargeant et al, 2010. RCTs performed in laboratory animal research showed similar methodological problems: an overview of 31 systematic reviews found that only 29% of studies reported randomization, 15% of studies reported allocation concealment, and 35% of studies reported blinded outcome assessment (Hirst et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The potential for false-positive results is often obscured because published manuscripts generally only report tests that achieved statistical significance, rather than indicate every test that was performed or explored. 3,12 A clearly defined primary research question can help mitigate the risk of excessively high rates of falsepositive results. An efficient study design formulated on the basis of specific, relevant hypotheses is one of the central protections against multiplicity 21 because it tends to limit the number of subgroups and other sources of multiple comparisons.…”
Section: Using An Appropriate Analytic Planmentioning
confidence: 99%
“…As veterinarians become increasingly familiar with the principles of evidence-based medicine, they are looking to the results of clinical trials to guide their practice. However, the methodological quality of published veterinary clinical trials is often poor, [1][2][3][4] which means that readers could draw incorrect conclusions from trial results and in turn make unfounded changes in patient care. Results of a recent review of study power in reports of small animal trials indicated that not only did most trials contain methodological flaws, but only a handful of studies even stated the primary research question.…”
mentioning
confidence: 99%